Placental Abruption with Subamniotic Hemorrhage: A Case Report - Juseok Yang; Jina Lee; Dong Hyung Lee (Clinical and Experimental Obstetrics & Gynecology)
Background: Subamniotic hemorrhage is a rare lesion with abnormal ultrasonographic findings that is caused by placental abruption. We report the case of a patient with placental abruption who presented with antepartum bleeding in whom the ultrasound findings of subamniotic hemorrhage were detected. This resulted in early diagnosis, leading to a favorable clinical outcome in this patient. Case: A primigravid 35-year-old woman visited the emergency room due to vaginal bleeding at 36 + 4 weeks of gestation. Ultrasound examination revealed a subamniotic hemorrhage that had not been evident on previous antenatal ultrasonography. An emergent cesarean section was performed, and the diagnosis of placental abruption was confirmed. The patient and baby were discharged after an uneventful course in the hospital. Conclusions: Detection of subamniotic hemorrhage by ultrasound helped in achieving an early diagnosis that resulted in prompt intervention against acute placental abruption and ensured favorable clinical outcomes. A thorough ultrasound examination of the placenta should be performed when managing patients with antepartum bleeding.